Silicon-carbon negative electrode binder as well as preparation method and application thereof

By using free radical polymerization binders of konjac glucomannan, acrylamide and glycidyl methacrylate, the adhesion between the silicon carbon negative electrode and the current collector is enhanced, and the problem of poor adhesion of the silicon-based negative electrode is solved, which significantly improves the problem of significant adhesion of the silicon-based negative electrode. The cycle stability of the battery and the electrode capacity retention rate are achieved.

CN119220209APending Publication Date: 2024-12-31CHINA ENFI ENG CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411374730.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the bonding properties of the silicon-based negative electrode adhesive and the silicon-based negative electrode are poor, resulting in large volume changes during the charge and discharge process, the active material is prone to peel off and fall off, the electrode capacity drops rapidly, and the circulation performance is poor.

Method used

The multi-component three-dimensional network polymer obtained by radical polymerization of konjac glucomannan, acrylamide and glycidyl methacrylate are used as silicon carbon negative electrode binder to enhance the bonding force through hydrogen bonding and covalent bonding to improve the bonding force. Adhesion between silicon-carbon negative electrode and current collector.

Benefits of technology

The circulation stability of the silicon carbon negative electrode is significantly improved, the peeling of active components caused by electrode powdering is avoided, and the circulation performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode binder as well as a preparation method and application thereof. The silicon-carbon negative electrode binder is a free radical polymerization binder and is prepared from the following raw materials: konjac glucomannan, acrylamide and glycidyl methacrylate. The silicon-carbon negative electrode binder is a multi-component three-dimensional network polymer obtained by free radical polymerization of konjac glucomannan, acrylamide and glycidyl methacrylate, contains rich hydroxyl groups, amino groups and epoxy groups, and can form hydrogen bonds with hydroxyl groups on the surface of a silicon-carbon negative electrode; and the acting force between the silicon-based negative electrode and the copper foil can be enhanced, the binding property is good, the integrity of the electrode structure can be maintained, and the active component stripping caused by electrode pulverization is avoided, so that the cycling stability of the silicon-carbon negative electrode is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-carbon negative electrode binder, a preparation method and application thereof. Background Art

[0002] Silicon has a high theoretical specific capacity (4200mAh g -1 ), low operating voltage and abundant reserves, it is very likely to replace graphite negative electrode materials as the next generation of high energy density lithium-ion battery negative electrode materials. However, the huge volume change (up to 300%) of silicon during the lithium insertion and extraction process will destroy the integrity of the electrode, resulting in a rapid decline in electrode capacity. At present, the scientific community has recognized that binders can greatly improve the cycle stability of silicon negative electrodes. However, traditional polyvinylidene fluoride (PVDF) binders are not suitable for silicon-based negative electrodes due to their weak van der Waals interaction with silicon materials and copper current collectors.

[0003] CN109103455A discloses a lithium-ion battery silicon-based negative electrode binder, which is synthesized from raw materials gellan gum and chloroacetic acid in a certain proportion. The molecular weight of gellan gum is a linear anionic heteropolysaccharide of more than 1 million, and its monosaccharide molecules are glucose, rhamnose and glucuronic acid, respectively, with a mass ratio of 2:1:1, and the molecular weight of chloroacetic acid is 94.5, the molecular formula is C2H3ClO2, and the purity is greater than 99%. CN107170989A discloses a lithium-ion battery silicon-based negative electrode material binder, which is composed of raw materials sodium hyaluronate and sodium alginate in a certain proportion. However, the bonding property of the binder obtained by the above scheme to the silicon-based negative electrode still needs to be improved. Summary of the invention

[0004] The main purpose of the present invention is to provide a silicon-carbon negative electrode binder, a preparation method and application thereof, so as to solve the problem that the bonding between the binder and the silicon-based negative electrode in the prior art is poor, and the active material is easily peeled off due to the large volume change of the silicon-based negative electrode during the charge and discharge process, and the electrode capacity decreases rapidly, thereby leading to poor battery cycle performance.

[0005] In order to achieve the above object, according to one aspect of the present invention, a silicon-carbon negative electrode binder is provided. The silicon-carbon negative electrode binder is a free radical polymerization binder. The raw materials of the silicon-carbon negative electrode binder include konjac glucomannan, acrylamide and glycidyl methacrylate.

[0006] Furthermore, the weight ratio of konjac glucomannan to acrylamide is 1:(0.05-5); and / or the weight ratio of konjac glucomannan to glycidyl methacrylate is 1:(0.1-2).

[0007] Furthermore, the weight average molecular weight of konjac glucomannan is 1 million to 2 million.

[0008] According to another aspect of the present invention, a method for preparing the above-mentioned silicon-carbon negative electrode binder of the present invention is provided, comprising the following steps: step S1, stirring and mixing konjac glucomannan and water to obtain a first solution; step S2, under an inert atmosphere, dripping an initiator aqueous solution into the first solution to obtain a second solution; step S3, dripping an acrylamide aqueous solution into the second solution to obtain a third solution; step S4, dripping an aqueous solution of glycidyl methacrylate into the third solution to obtain a fourth solution; step S5, stirring and polymerizing the fourth solution to obtain a silicon-carbon negative electrode binder.

[0009] Furthermore, in step S1, the mass concentration of the first solution is 10-50%; and / or the stirring temperature is 30-80°C, and the stirring speed is 100-1000 r·min -1 , stirring time is 30 to 90 minutes.

[0010] Further, in step S2, the inert atmosphere includes one or more of nitrogen, argon and helium; and / or the initiator includes one or more of ammonium persulfate, sodium persulfate, potassium persulfate and potassium persulfate-sodium bisulfite; and / or the mass concentration of the initiator aqueous solution is 1 to 20%; and / or the dripping speed of the ammonium persulfate aqueous solution is 1 to 5 mL / min; and / or the volume ratio of the first solution to the initiator is 1:(0.1 to 0.5).

[0011] Furthermore, in step S3, the mass concentration of the acrylamide aqueous solution is 5-50%; and / or the dripping speed of the acrylamide aqueous solution is 5-10 mL / min; and / or the volume ratio of the first solution to the acrylamide aqueous solution is 1:(0.1-5).

[0012] Further, in step S4, the mass concentration of the aqueous solution of glycidyl methacrylate is 5-80%; and / or the dripping speed of the glycidyl methacrylate solution is 5-10 mL / min; and / or the volume ratio of the first solution to the glycidyl methacrylate solution is 1:(0.2-1.2); and / or in step S5, the temperature of the stirring polymerization is 30-80°C, and the time is 0.5-1.5 h; preferably, after the stirring polymerization is completed, step S5 also includes a step of post-treating the reaction liquid, and the post-treatment includes: using anhydrous ethanol to centrifuge the reaction liquid, and then vacuum drying or freeze-drying to obtain a silicon-carbon negative electrode binder.

[0013] According to another aspect of the present invention, there is provided a silicon-carbon negative electrode plate, comprising the silicon-carbon negative electrode binder of the present invention, or the silicon-carbon negative electrode binder obtained by the preparation method of the present invention.

[0014] According to another aspect of the present invention, a battery is provided, comprising the above-mentioned silicon-carbon negative electrode plate of the present invention.

[0015] The silicon-carbon negative electrode binder of the present invention is a multi-component three-dimensional network polymer obtained by free radical polymerization of konjac glucomannan, acrylamide and glycidyl methacrylate, and contains rich hydroxyl, amino and epoxy groups. It can not only form hydrogen bonds with the hydroxyl groups on the surface of the silicon-carbon negative electrode, but also enhance the interaction between the silicon-based negative electrode and the copper foil. It has good adhesion, can maintain the integrity of the electrode structure, and avoid the peeling of active components caused by electrode pulverization, thereby significantly improving the cycle stability of the silicon-carbon negative electrode. DETAILED DESCRIPTION

[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0017] As described in the background of the present invention, the prior art has the problem that the bonding between the binder and the silicon-based negative electrode is poor, and the active material is easily peeled off due to the large volume change of the silicon-based negative electrode during the charge and discharge process, and the electrode capacity decreases rapidly, which leads to poor battery cycle performance. In order to solve the above problems, in a typical embodiment of the present invention, a silicon-carbon negative electrode binder is provided, and the silicon-carbon negative electrode binder is a free radical polymerization binder, and the raw materials of the silicon-carbon negative electrode binder include konjac glucomannan, acrylamide and glycidyl methacrylate.

[0018] The silicon-carbon negative electrode binder of the present invention is obtained by free radical polymerization of konjac glucomannan (KGM), acrylamide (AM) and glycidyl methacrylate (GMA). Konjac glucomannan is a polysaccharide mainly composed of β-(1,4)-linked d-mannose and d-glucose, with a molar ratio of 1.6:1, and also contains a small amount of acetylated groups, rich in hydroxyl functional groups, but its toughness is poor, which limits its further application. Based on this, the present invention introduces polyacrylamide into konjac glucomannan, which can improve the toughness of the binder and solve the brittleness problem of polysaccharides. The polar amino groups on the polyacrylamide can also form hydrogen bonds with the hydroxyl groups on the surface of silicon particles, thereby increasing the interfacial bonding force. At the same time, glycidyl methacrylate is introduced, and the epoxy groups on it open the ring to form covalent bonds with the hydroxyl groups on the surface of silicon particles, further increasing the interfacial bonding force.

[0019] The silicon-carbon negative electrode binder of the present invention is a multi-component three-dimensional network polymer (KPG), which is rich in hydroxyl, amino and epoxy groups. It can not only form hydrogen bonds with the hydroxyl groups on the surface of the silicon-carbon negative electrode, thereby having significantly enhanced bonding with the silicon-carbon negative electrode, but also enhance the interaction between the silicon-based negative electrode and the current collector (such as copper foil). It has good bonding properties, can maintain the integrity of the electrode structure, and avoid the peeling of active components caused by electrode pulverization, thereby significantly improving the cycle stability of the silicon-carbon negative electrode. It is a potential silicon-carbon negative electrode material binder.

[0020] In a preferred embodiment, the weight ratio of konjac glucomannan to acrylamide is 1:(0.05-5); and / or the weight ratio of konjac glucomannan to glycidyl methacrylate is 1:(0.1-2), so that acrylamide and glycidyl methacrylate can be better utilized to improve the toughness of the binder, so that the silicon-carbon negative electrode binder contains more hydroxyl, amino and epoxy groups, thereby enhancing the hydrogen bonding effect between the binder and the surface hydroxyl groups of the silicon-carbon negative electrode, further increasing the interfacial bonding force and improving the cycle performance.

[0021] In order to provide sufficient hydroxyl functional groups to enhance the adhesion between the binder and the silicon-based negative electrode, and between the silicon-based negative electrode and the current collector, while making the solution viscosity appropriate during the preparation process to facilitate preparation, in a preferred embodiment, the weight average molecular weight of konjac glucomannan is 1 million to 2 million.

[0022] In another typical embodiment of the present invention, a method for preparing the above-mentioned silicon-carbon negative electrode binder of the present invention is also provided, comprising the following steps: step S1, stirring and mixing konjac glucomannan and water to obtain a first solution; step S2, under an inert atmosphere, dripping an initiator aqueous solution into the first solution to obtain a second solution; step S3, dripping an acrylamide aqueous solution into the second solution to obtain a third solution; step S4, dripping an aqueous solution of glycidyl methacrylate into the third solution to obtain a fourth solution; step S5, stirring and polymerizing the fourth solution to obtain a silicon-carbon negative electrode binder.

[0023] The invention firstly stirs and mixes konjac glucomannan and water to obtain a konjac glucomannan aqueous solution; then drips an initiator aqueous solution under an inert atmosphere to remove air in a reaction container and a solution to prevent oxygen or moisture therein from affecting a polymerization reaction, thereby obtaining a second solution containing an initiator; then drips an acrylamide aqueous solution and a glycidyl methacrylate aqueous solution into the second solution, and stirs and polymerizes them; under the action of the initiator, a free radical polymerization reaction occurs between the three raw materials, thereby obtaining a silicon-carbon negative electrode binder.

[0024] Among them, the introduction of polyacrylamide improves the toughness of the binder to solve the brittleness problem of konjac glucomannan. The polar amino groups on polyacrylamide can form hydrogen bonds with the hydroxyl groups on the surface of silicon particles, thereby increasing the interfacial adhesion. The cross-linking of the epoxy groups on glycidyl methacrylate helps to enhance the toughness of the polysaccharide and increase the cohesion of the binder. The epoxy groups open the ring to form covalent bonds with the hydroxyl groups on the surface of silicon particles, increasing the interfacial adhesion.

[0025] The preparation method is simple in process, easy to operate, has low raw material cost, and is green and environmentally friendly. The prepared binder has significantly enhanced bonding strength with the silicon-carbon negative electrode, which can further enhance the bonding strength between the silicon-carbon negative electrode and the current collector, reduce the peeling off of active materials caused by the large volume change of the silicon-based negative electrode during the charge and discharge process, reduce the decrease in electrode capacity, and thus enable the battery to have good cycle performance.

[0026] In order to further improve the uniformity of the solution and facilitate the subsequent free radical polymerization reaction, in a preferred embodiment, in step S1, the mass concentration of the first solution is 10-50%; and / or the stirring temperature is 30-80°C, and the stirring speed is 100-1000 r·min -1 , stirring time is 30 to 90 minutes.

[0027] In a preferred embodiment, in step S2, the inert atmosphere includes one or more of nitrogen, argon and helium; and / or the initiator includes a medium temperature initiator and / or a low temperature initiator; preferably, it includes one or more of ammonium persulfate, sodium persulfate, potassium persulfate and potassium persulfate-sodium bisulfite; the above initiators are more suitable for the polymerization system of the present invention, and can further increase the rate of the polymerization reaction. And / or the mass concentration of the initiator aqueous solution is 1-20%; and / or the dripping speed of the ammonium persulfate aqueous solution is 1-5mL / min; and / or the volume ratio of the first solution to the ammonium persulfate aqueous solution is 1:(0.1-0.5), so as to further improve the uniformity of the solution, so as to be more conducive to the subsequent free radical polymerization reaction.

[0028] In order to further increase the polymerization rate of acrylamide, thereby better improving the toughness of the binder and increasing the interfacial bonding force, based on similar reasons, in a preferred embodiment, in step S3, the mass concentration of the acrylamide aqueous solution is 5-50%; and / or the dripping speed of the acrylamide aqueous solution is 5-10 mL / min; and / or the volume ratio of the first solution to the acrylamide aqueous solution is 1:(0.1-5).

[0029] In order to better open the epoxy groups on the glycidyl methacrylate and form covalent bonds with the hydroxyl groups on the surface of the silicon particles, thereby further increasing the interfacial adhesion, in a preferred embodiment, in step S4, the mass concentration of the glycidyl methacrylate aqueous solution is 5-80%; and / or the dripping speed of the glycidyl methacrylate solution is 5-10 mL / min; and / or the volume ratio of the first solution to the glycidyl methacrylate solution is 1:(0.2-1.2); and / or in step S5, the stirring polymerization temperature is 30-80°C and the time is 0.5-1.5 h; preferably, after the stirring polymerization is completed, step S5 also includes a step of post-treating the reaction liquid, and the post-treatment includes: using anhydrous ethanol to centrifuge the reaction liquid, and then vacuum drying or freeze-drying to obtain a silicon-carbon negative electrode binder. Under the above conditions, the bonding properties of the polymerization product can be further improved, thereby better maintaining the integrity of the electrode structure and avoiding the peeling of active components caused by electrode pulverization, so as to further significantly improve the cycle stability of the silicon-carbon negative electrode.

[0030] In another typical embodiment of the present invention, a silicon-carbon negative electrode plate is provided, comprising the silicon-carbon negative electrode binder of the present invention, or the silicon-carbon negative electrode binder obtained by the preparation method of the present invention. Since the binder with good adhesion of the present invention is used, the integrity of the electrode structure can be well maintained, avoiding the peeling of active components and the decrease of electrode capacity due to electrode pulverization.

[0031] In another typical embodiment of the present invention, a battery is provided, comprising the silicon-carbon negative electrode sheet of the present invention, which has significantly improved cycle stability.

[0032] Typically but not limiting, the weight ratio of konjac glucomannan to acrylamide is 1:0.05, 1:0.08, 1:0.1, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or a range consisting of any two of them.

[0033] Typically but not limiting, the weight ratio of konjac glucomannan to glycidyl methacrylate is 1:0.1, 1:0.2, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2 or a range consisting of any two of them.

[0034] Typically but not limiting, in step S5, the temperature of the stirring polymerization is 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, and the time is 0.5h, 0.6h, 0.8h, 1.0h, 1.2h, 1.4h, 1.5h or a range consisting of any two of them.

[0035] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0036] Unless otherwise specified, the physicochemical properties of konjac glucomannan (KGM), acrylamide (AM) and glycidyl methacrylate (GMA) used in the following examples and comparative examples are as follows:

[0037] Konjac glucomannan (KGM): molecular weight about 1 million;

[0038] Acrylamide (AM): molecular weight is 71.08, chemical formula is C3H5NO, purity is greater than 99%;

[0039] Glycidyl methacrylate (GMA): molecular weight is 142.15, chemical formula is C7H 10 O3, purity greater than 99%.

[0040] Example 1

[0041] Step S1, 1.0 g KGM and 50 mL deionized water were mixed in a four-necked round-bottomed flask to form a 20 wt% KGM aqueous solution; the four-necked round-bottomed flask was placed in a 70° C. constant temperature water bath and mechanically stirred at a stirring speed of 400 r·min -1 , the stirring time is set to 30min; prepare a 20wt% APS (ammonium persulfate) aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0042] Step S2, open the valve of the constant pressure funnel containing the initiator APS, and add 10 mL of the APS aqueous solution dropwise at a rate of 3 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0043] Step S3, open the valve of the constant pressure funnel containing AM, and add 10 mL of AM aqueous solution dropwise at a rate of 8 mL / min (the weight ratio of KGM to AM is 1:0.4);

[0044] Step S4, open the valve of the constant pressure funnel containing GMA, and add 10 mL of GMA aqueous solution dropwise at a rate of 8 mL / min (the weight ratio of KGM to GMA is 1:0.4);

[0045] Step S5, continue stirring for 1 hour and then stop heating in a 70° C. water bath, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-1.

[0046] Example 2

[0047] Step S1, 2.5 g KGM and 50 mL deionized water were mixed in a four-necked round-bottomed flask to form a 50 wt% KGM aqueous solution; the four-necked round-bottomed flask was placed in a 70° C. constant temperature water bath and mechanically stirred at a stirring speed of 400 r·min -1 , the stirring time is set to 30min; prepare a 20wt% APS aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0048] Step S2, open the valve of the constant pressure funnel containing the initiator APS, and add 10 mL of the APS aqueous solution dropwise at a rate of 1 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0049] Step S3, open the valve of the constant pressure funnel containing AM, and add 5 mL of AM aqueous solution dropwise at a rate of 5 mL / min (the weight ratio of KGM to AM is 1:0.4);

[0050] Step S4, open the valve of the constant pressure funnel containing GMA, and add 10 mL of GMA aqueous solution dropwise at a rate of 5 mL / min (the weight ratio of KGM to GMA is 1:0.4);

[0051] Step S5, continue stirring for 1 hour and then stop heating in a 70° C. water bath, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-2.

[0052] Example 3

[0053] Step S1, 1.0 g KGM and 50 mL deionized water were mixed in a four-necked round-bottomed flask to form a 20 wt% KGM aqueous solution; the four-necked round-bottomed flask was placed in a 70° C. constant temperature water bath and mechanically stirred at a stirring speed of 400 r·min -1, the stirring time is set to 30min; prepare a 1wt% APS aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0054] Step S2, open the valve of the constant pressure funnel containing the initiator APS, and add 20 mL of the APS aqueous solution dropwise at a rate of 5 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0055] Step S3, open the valve of the constant pressure funnel containing AM, and add 40 mL of AM aqueous solution dropwise at a rate of 10 mL / min (the weight ratio of KGM to AM is 1:0.4);

[0056] Step S4, open the valve of the constant pressure funnel containing GMA, and add 40 mL of GMA aqueous solution dropwise at a rate of 10 mL / min (the weight ratio of KGM to GMA is 1:0.4);

[0057] Step S5, continue stirring for 1 hour and then stop heating in a 70° C. water bath, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-3.

[0058] Example 4

[0059] Step S1, 1.0 g KGM and 50 mL deionized water were mixed in a four-necked round-bottomed flask to form a 20 wt% KGM aqueous solution; the four-necked round-bottomed flask was placed in a 70° C. constant temperature water bath and mechanically stirred at a stirring speed of 400 r·min -1 , the stirring time is set to 60min; prepare a 20wt% APS aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 5wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0060] Step S2, open the valve of the constant pressure funnel containing the initiator APS, and add 10 mL of the APS aqueous solution dropwise at a rate of 1 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0061] Step S3, open the valve of the constant pressure funnel containing AM, and add 20 mL of AM aqueous solution dropwise at a rate of 10 mL / min (the weight ratio of KGM to AM is 1:0.4);

[0062] Step S4, open the valve of the constant pressure funnel containing GMA, and add 20 mL of GMA aqueous solution dropwise at a rate of 10 mL / min (the weight ratio of KGM to GMA is 1:0.4);

[0063] Step S5, continue stirring for 1 hour and then stop heating in a 70° C. water bath, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-4.

[0064] Example 5

[0065] Step S1, 1.0 g KGM and 50 mL deionized water were mixed in a four-necked round-bottomed flask to form a 20 wt% KGM aqueous solution; the four-necked round-bottomed flask was placed in a 70° C. constant temperature water bath and mechanically stirred at a stirring speed of 400 r·min -1 , the stirring time is set to 60min; prepare a 20wt% APS aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 40wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 5wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0066] Step S2, open the valve of the constant pressure funnel containing the initiator APS, and add 5 mL of the APS aqueous solution dropwise at a rate of 5 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0067] Step S3, open the valve of the constant pressure funnel containing AM, and add 60 mL of AM aqueous solution dropwise at a rate of 10 mL / min (the weight ratio of KGM to AM is 1:0.4);

[0068] Step S4, open the valve of the constant pressure funnel containing GMA, and add 40 mL of GMA aqueous solution dropwise at a rate of 10 mL / min (the weight ratio of KGM to GMA is 1:0.4);

[0069] Step S5, continue stirring for 1 hour and then stop heating in a 70° C. water bath, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-5.

[0070] Example 6

[0071] Step S1, 0.5 g KGM (weight average molecular weight of about 1 million) and 50 mL deionized water were mixed in a four-necked round-bottom flask to form a 10 wt% KGM aqueous solution; the four-necked round-bottom flask was placed in a 30° C. constant temperature water bath and mechanically stirred at a stirring speed of 100 r·min -1 , the stirring time is set to 90min; prepare a 20wt% initiator (sodium persulfate) aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 5wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 5wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0072] Step S2, open the valve of the constant pressure funnel containing the initiator (sodium persulfate), and add 10 mL of the initiator (sodium persulfate) aqueous solution dropwise at a rate of 3 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0073] Step S3, open the valve of the constant pressure funnel containing AM, and add 5 mL of AM aqueous solution dropwise at a rate of 8 mL / min (the weight ratio of KGM to AM is 1:0.05);

[0074] Step S4, open the valve of the constant pressure funnel containing GMA, and add 10 mL of GMA aqueous solution dropwise at a rate of 8 mL / min (the weight ratio of KGM to GMA is 1:0.1);

[0075] Step S5, continue stirring for 0.5h and then stop heating in a water bath at 80°C, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-1.

[0076] Example 7

[0077] Step S1, 2.5 g KGM (weight average molecular weight of about 2 million) and 50 mL deionized water are mixed in a four-necked round-bottom flask to form a 50 wt% KGM aqueous solution; the four-necked round-bottom flask is placed in a constant temperature water bath at 80° C. and mechanically stirred at a stirring speed of 1000 r·min -1 , the stirring time is set to 30min; prepare a 20wt% initiator (potassium persulfate-sodium bisulfite) aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare a 50wt% AM aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; prepare an 80wt% GMA aqueous solution, transfer it to a constant pressure funnel, and place it on a four-necked flask; then introduce nitrogen into the round-bottom flask for half an hour to remove the air in the four-necked flask and the solution;

[0078] Step S2, open the valve of the constant pressure funnel containing the initiator (potassium persulfate-sodium bisulfite), and add 25 mL of the initiator (potassium persulfate-sodium bisulfite) aqueous solution dropwise at a rate of 3 mL / min. After the addition of the initiator is completed, continue stirring for half an hour;

[0079] Step S3, open the valve of the constant pressure funnel containing AM, and add 250 mL of AM aqueous solution dropwise at a rate of 8 mL / min (the weight ratio of KGM to AM is 1:5);

[0080] Step S4, open the valve of the constant pressure funnel containing GMA, and add 60 mL of GMA aqueous solution dropwise at a rate of 8 mL / min (the weight ratio of KGM to GMA is 1:1.92);

[0081] Step S5, continue stirring for 1.5 hours and then stop heating in a 30° C. water bath, close the vent after cooling, centrifuge the obtained solution with anhydrous ethanol, and then vacuum dry to obtain the silicon-carbon negative electrode binder KPG-1.

[0082] Comparative Example 1

[0083] Weigh 1.0 g of KGM, disperse it in a certain amount of deionized water, and prepare an aqueous solution with a mass concentration of 5% as a binder.

[0084] Comparative Example 2

[0085] 1.0 g of PVDF powder was weighed and dispersed in a certain amount of deionized water to prepare an aqueous solution with a mass concentration of 5%, which was used as a binder.

[0086] The silicon-based negative electrode binder obtained in each embodiment and comparative example is used to prepare a silicon-based negative electrode plate, and assembled into a button-type half-cell. The theoretical specific capacity of the silicon-carbon material used in the present invention is about 600 mAh / g. The specific operation is as follows: the silicon-carbon active material: conductive carbon black: binder = 8:1:1 mass ratio is mixed, deionized water is used as a solvent for slurrying, and then the slurry is coated on a copper foil. After vacuum drying at 100°C for 10 hours, the plate is taken out, the plate is cut and the button-type battery is assembled. Among them, the electrolyte uses a silicon-carbon electrolyte, and the diaphragm uses a PP material diaphragm.

[0087] The obtained button battery was left to stand at 25±2℃ for 12h, and then the charge and discharge test was carried out on a charge and discharge tester (NEWARE BTS-5V / 10mA produced by Shenzhen Newwell Electronics Co., Ltd.). The charge and discharge voltage range was 0.005~2.0V, and the current density was 0.1C. The first cycle charge specific capacity, first cycle coulomb efficiency and 100 cycle performance were tested respectively. The electrochemical test results are shown in Table 1.

[0088] Table 1

[0089] sample First cycle coulomb efficiency (%) First cycle charge capacity (mAh / g) 100 cycles capacity retention rate (%) Example 1 88.7 586.2 90.5 Example 2 86.5 579.3 88.2 Example 3 83.8 566.2 85.6 Example 4 81.3 561.7 83.5 Example 5 80.2 553.4 79.2 Example 6 79.9 543.8 77.6 Example 7 79.7 548.1 76.9 Comparative Example 1 76.6 508.6 60.2 Comparative Example 2 72.5 463.5 52.8

[0090] As can be seen from the above, compared with the comparative example, the silicon-carbon negative electrode binder of the present invention is a multi-component three-dimensional network polymer obtained by free radical polymerization of konjac glucomannan, acrylamide and glycidyl methacrylate, which contains rich hydroxyl, amino and epoxy groups, and can not only form hydrogen bonds with the hydroxyl groups on the surface of the silicon-carbon negative electrode, but also enhance the interaction between the silicon-based negative electrode and the copper foil, and has good adhesion, and can maintain the integrity of the electrode structure, and avoid the peeling of active components caused by electrode pulverization, thereby significantly improving the cycle stability of the silicon-carbon negative electrode. In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the comprehensive effect of the material is better.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A silicon-carbon negative electrode binder, characterized in that: The silicon-carbon negative electrode binder is a free radical polymerization binder, and the raw materials of the silicon-carbon negative electrode binder include konjac glucomannan, acrylamide and glycidyl methacrylate.

2. The silicon-carbon negative electrode binder according to claim 1, characterized in that: The weight ratio of the konjac glucomannan to the acrylamide is 1:(0.05-5); and / or The weight ratio of the konjac glucomannan to the glycidyl methacrylate is 1:(0.1-2).

3. The silicon-carbon negative electrode binder according to claim 1 or 2, characterized in that: The weight average molecular weight of the konjac glucomannan is 1 million to 2 million.

4. The method for preparing the silicon-carbon negative electrode binder according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step S1, stirring and mixing konjac glucomannan and water to obtain a first solution; Step S2, under an inert atmosphere, dropwise adding an initiator aqueous solution into the first solution to obtain a second solution; Step S3, adding an aqueous solution of acrylamide dropwise to the second solution to obtain a third solution; Step S4, adding a glycidyl methacrylate aqueous solution dropwise to the third solution to obtain a fourth solution; Step S5, stirring and polymerizing the fourth solution to obtain the silicon-carbon negative electrode binder.

5. The preparation method according to claim 4, characterized in that: In the step S1, The mass concentration of the first solution is 10-50%; and / or The stirring temperature is 30-80°C and the stirring speed is 100-1000 r·min -1 , stirring time is 30 to 90 minutes.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, The inert atmosphere comprises one or more of nitrogen, argon and helium; and / or The initiator comprises one or more of ammonium persulfate, sodium persulfate, potassium persulfate and potassium persulfate-sodium bisulfite; and / or The mass concentration of the initiator aqueous solution is 1 to 20%; and / or The dropping speed of the ammonium persulfate aqueous solution is 1 to 5 mL / min; and / or The volume ratio of the first solution to the initiator is 1:(0.1-0.5).

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step S3, the mass concentration of the acrylamide aqueous solution is 5-50%; and / or The dropping speed of the acrylamide aqueous solution is 5 to 10 mL / min; and / or The volume ratio of the first solution to the aqueous acrylamide solution is 1:(0.1-5).

8. The preparation method according to any one of claims 4 to 7, characterized in that In the step S4, the mass concentration of the glycidyl methacrylate aqueous solution is 5-80%; and / or the dripping speed of the glycidyl methacrylate solution is 5-10 mL / min; and / or the volume ratio of the first solution to the glycidyl methacrylate solution is 1:(0.2-1.2); and / or In the step S5, the temperature of the stirring polymerization is 30-80°C, and the time is 0.5-1.5h; preferably, after the stirring polymerization is completed, the step S5 also includes a step of post-treating the reaction liquid, and the post-treatment includes: using anhydrous ethanol to centrifuge the reaction liquid, and then vacuum drying or freeze-drying to obtain the silicon-carbon negative electrode binder.

9. A silicon-carbon negative electrode plate, characterized in that: The invention comprises the silicon-carbon negative electrode binder according to any one of claims 1 to 3, or the silicon-carbon negative electrode binder obtained by the preparation method according to any one of claims 4 to 8.

10. A battery, characterized in that: Including the silicon-carbon negative electrode sheet as described in claim 9.